A Research on Innovation in Small and Medium-Sized Enterprises: The Case of Kazakhstan - Kurmanov, Nurlan; Dametken Turekulova, Dametken; Doskeyeva, Gulashar; Alina, Gulzhan (International Journal of Economics and Financial Issues, 2016)
The purpose of this study was to determine key factors that have a major influence on innovative activity of the SME in Kazakhstan. In this paper, statistical analysis of indicators of innovative growth in the Republic of Kazakhstan was conducted. The indicators were compared to those of technologically advanced countries, in particular to such indices as: the share of innovation-active enterprises, domestic spending on research and development (percentage to GDP), total researchers equivalent per thousand total employments, and amount of researches conducted. As the results of the research, key factors that have a major influence on innovative activity of the SME were determined. Keywords: Innovative Activities; Small and Medium-sized Enterprises; Kazakhstan. JEL Classifications: M13, O32